ESTG_EDP: External sorting as a Tool Used to Process Gas Holder Details Using Early Data Preprocessing - Hrushikesava Raju, S; Nagabhushana Rao, M (International Journal of Computer Sciences and Engineering, 2025)
This paper takes external sorting as a tool in which processing made simpler. External sorting usually processes the huge data stored on the external storage devices such as a tape, disks or flash or combination etc. When there is huge gas holders details stored in a database, Some process is required in order to process the operations like filtering (sorting), searching over the gas holders details. The kind of sorting (process) required is external sorting which is used to process huge data (databases or big data) available on secondary storage devices. The external sorting is a useful and efficient technique to perform the operations on the gas holders database. To process the information and producing reports or results, an automated tool is required which asks required user details for processing the searching operation, filtering operation is to be performed if any duplication is found in the data set. The results are specified or illustrated in the Results chapter. Data pre-processing is required when there is any inconsistency present in the given dataset which set-right into quality or neat data set.